2011
DOI: 10.1002/eji.201041197
|View full text |Cite
|
Sign up to set email alerts
|

IL‐22 and TNF‐α represent a key cytokine combination for epidermal integrity during infection with Candida albicans

Abstract: T cells exercise their full impact on target cells through a combination of secreted cytokines. The recently described T helper cell subset Th22 is characterized by a combinatorial secretion of IL-22 and TNF-a. Here, we demonstrate that IL-22 increases the TNF-adependent induction and secretion of several immune-modulatory molecules such as initial complement factors C1r and C1s, antimicrobial peptides S100A7 and HBD-2 (human b defensin 2), and antimicrobial chemokines CXCL-9/-10/-11 in primary human keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 35 publications
3
105
0
6
Order By: Relevance
“…Both cytokines are produced by Th22 cells and can synergistically induce an effective innate immune response of epithelial cells during C. albicans infection, conferring protection in humans (Eyerich et al, 2011). Our results indicate that there are potential microbial factors that correlate with the production of both cytokines.…”
Section: Functional Associations With Fungal-induced Cytokine Responsesmentioning
confidence: 66%
“…Both cytokines are produced by Th22 cells and can synergistically induce an effective innate immune response of epithelial cells during C. albicans infection, conferring protection in humans (Eyerich et al, 2011). Our results indicate that there are potential microbial factors that correlate with the production of both cytokines.…”
Section: Functional Associations With Fungal-induced Cytokine Responsesmentioning
confidence: 66%
“…2A). To determine whether the IL-22 + cells in our experiments match the phenotype of previously described Th22 cells, we assessed whether these cells coexpressed TNF-a, a characteristic of Th22 cells (15,19,27). Indeed, most IL-22 + cells coexpressed TNF-a (Fig.…”
Section: Il-22 Is Not Restricted To a Specific Th Cell Subsetmentioning
confidence: 76%
“…73 In primary human keratinocytes, IL-22 plus TNF-a effectively inhibit the growth of C. albicans and maintain the survival of epithelia. 85 In addition, human vaginal epithelial cells could express S100 calcium-binding proteins to recruit polymorphonuclear neutrophils (PMNs) to the C. albicans-infected vagina. 86 Recently it was shown that S100A8 alarmin is sufficient, but not necessary, to induce PMN migration during experimental vaginal candidiasis.…”
Section: Prrs Of Epithelial Cellsmentioning
confidence: 99%